Three-dimensional Volume Changes of the Reconstructed Breast Following DIEP Flap Breast Reconstruction - Lee, Mi Kyung; Park, Hae Yeon; Park, Jin-Woo; Mun, Goo-Hyun; Woo, Kyong-Je (Journal of Reconstructive Microsurgery, 2022)
Background This study aimed to assess whether the reconstructed breast volume changed postoperatively following a deep inferior epigastric artery perforator (DIEP) flap.Methods Patients were included if they had undergone unilateral breast reconstruction with a DIEP flap at the two selected centers between April 2017 and September 2019. Serial 3-D surface imaging of both breasts was taken at 1, 3, 6, and 12 months postoperatively. The primary outcome was a volume ratio of the reconstructed to the contralateral breast. A linear mixed-effect model was used to evaluate whether the DIEP flap volume changed according to the postoperative time.Results A total of 74 patients were included in the analysis. The mean volume ratio of the reconstructed side compared with the contralateral breast at 1, 3, 6, and 12 months postoperatively were 106.9%, 105.9%, 108.7%, and 107.6%, respectively. In the linear mixed effect model, the volume ratio of the reconstructed breast did not change over time for immediate reconstructions (p = 0.376). However, there was an increase over time in delayed reconstructions (p = 0.043). Adjuvant radiation, chemotherapy, and hormone therapy did not influence the volume ratio of the reconstruced breast. Correlation analysis using repeatedly measured values showed that both reconstruced and healthy breast volumes had positive correlation with the patient's body weight (p < 0.001). On the other hand, volume ratio of the breasts was not influenced by the patient's body weight (p = 0.493). The volume ratio of the reconstructed breast significantly decreased in the upper inner (p = 0.003) and the upper outer (p = 0.006) quadrants, while increasing in the lower outer (p = 0.002) quadrant throughout the first-year postoperative period.Conclusion The volume ratio of the reconstructed to the contralateral breast does not decrease postoperatively following DIEP flap breast reconstruction.
Keywords: DIEP flap; breast reconstruction; breast volume